2005
DOI: 10.1037/0021-843x.114.3.456
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations of Alcohol Dehydrogenase With Alcohol Use Disorders and Endophenotypes in White College Students.

Abstract: Associations of alcohol dehydrogenase (ADH) gene polymorphisms (ADH1B*2 and ADH1C*1) with a lifetime alcohol use disorder (AUD) were examined in White college students. Alcohol-related endophenotypes likely to be influenced by elevations in acetaldehyde were also assessed. Individuals with an ADH1B*2 allele had lower rates of AUDs, consumed a lower maximum number of drinks in a 24-hr period, reported a greater level of response to alcohol, were more likely to have experienced alcohol-induced headaches followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 113 publications
3
61
1
1
Order By: Relevance
“…This association has been seen for ADH1B*2 most clearly in Asians. 16,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] An association has also been reported in Jews, 44 Hispanics, 17,45 and non-Hispanic whites, 17,43,[46][47][48][49] as well as in a metaanalysis. 50 However, not all studies have found a correlation.…”
Section: Association Of Adh1b and Alcoholismmentioning
confidence: 99%
“…This association has been seen for ADH1B*2 most clearly in Asians. 16,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] An association has also been reported in Jews, 44 Hispanics, 17,45 and non-Hispanic whites, 17,43,[46][47][48][49] as well as in a metaanalysis. 50 However, not all studies have found a correlation.…”
Section: Association Of Adh1b and Alcoholismmentioning
confidence: 99%
“…We used the maximum number of drinks in a single day (Maxdrinks) variable (Saccone et al, 2000) that has been used previously in many studies (Dawson et al, 2010;Greenfi eld et al, 2006;Malone et al, 2002;Schuckit et al, 2002;Schumann et al, 2003;Wall et al, 2001Wall et al, , 2003Wall et al, , 2005, including in Israel (Hasin et al, 2002a;Spivak et al, 2007). The time frame for this variable was the last 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…While most evaluations of the impact of the ADH1B gene have focused on Asians, a group with a high prevalence of the ADH1B Ã 2 allele (Luczak et al, 2006), some data are available from other racial and ethnic groups (Borras et al, 2000;Carr et al, 2002;Gilder et al, 1993;Hasin et al, 2002aHasin et al, , 2002bLoew et al, 2003;Luczak et al, 2006;Marussin et al, 2004;Neumark et al, 1998Neumark et al, , 2004Ogurtsov et al, 2001;Wall et al, 2005). The ADH1B Ã 2 allele has been reported to be associated with a decreased risk for AUDs in white Europeans and Jews (Borras et al, 2000;Hasin et al, 2002b;Wall et al, 2005;Whitfield et al, 1998), linked to reduced alcohol consumption Loew et al, 2003;Neumark et al, 1998;Shea et al, 2001), and related to the LR to alcohol using a self-report instrument .…”
mentioning
confidence: 99%